A practical stable control scheme under end point equivalence modulation for DC power supply converters. Issue 14 (12th September 2021) - Li, Po; He, Ying; Lin, Xia; Guan, Mingjie
Abstract: A series of DC power supply converters can be described as linear affine systems with finite inputs and constrained switching frequency. In this study, a practical‐stability‐oriented general control framework with duty‐cycle‐like characteristics is deduced for such converters. First, a concept called End Point Equivalence Modulation (EPEM) is introduced to release constraints. Following this, a Control Lyapunov Function (CLF) is employed to design the switching law and the relationship between the boundary of the convergence zone and the switching frequency is derived. In addition, an optimized switching strategy is presented to halve the switching frequency without degrading the control performance, which is also helpful for reducing switching loss. Finally, a single‐phase inverter and buck converter are considered as case studies and analysis show that Sinusoidal Pulse Width Modulation (SPWM) and volt‐second balance guarantee their practical stability, respectively, which can be theoretically derived and proved under EPEM. All the proposed methods and controllers are validated both by simulations on MATLAB/Simulink and experiments in a rapid control prototype platform based on a FPGA module.